Efecto desplazamiento o complementariedad entre la inversión pública y la inversión privada caso peruano (2001- 2021) - López Balbín, Fidel (2023)
This article analyzes the impact of public investment on private investment habits. Access to financial resources from the private sector (companies and households) through taxes: IGV, ISC, rental taxes and others; taxpayers pay taxes at the expense of current consumption and stop investing. Second, the demand for currencies increases, which increases interest rates. Interest rates can have a negative impact on private investment.